2018
DOI: 10.3389/fphar.2018.00172
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Theories of Psychedelic Drug Effects

Abstract: How do psychedelic drugs produce their characteristic range of acute effects in perception, emotion, cognition, and sense of self? How do these effects relate to the clinical efficacy of psychedelic-assisted therapies? Efforts to understand psychedelic phenomena date back more than a century in Western science. In this article I review theories of psychedelic drug effects and highlight key concepts which have endured over the last 125 years of psychedelic science. First, I describe the subjective phenomenology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 228 publications
2
146
1
2
Order By: Relevance
“…Therefore, building a richer statistical description of the brain’s dynamics using recent information-theoretic tools (such as multivariate extensions of mutual information 28 or Integrated Information Theory, IIT 46 ) remains an exciting open problem. In fact, recent attempts of unifying IIT and the EBH in a single framework to understand the effects of psychedelic drugs 47 are helping to bridge the gap between the univariate EBH and the multivariate IIT.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, building a richer statistical description of the brain’s dynamics using recent information-theoretic tools (such as multivariate extensions of mutual information 28 or Integrated Information Theory, IIT 46 ) remains an exciting open problem. In fact, recent attempts of unifying IIT and the EBH in a single framework to understand the effects of psychedelic drugs 47 are helping to bridge the gap between the univariate EBH and the multivariate IIT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study showed that LSD attenuates top-down suppression of prediction error in response to surprising auditory stimuli, as measured by mismatch negativity in the auditory oddball paradigm (Timmermann et al, in press ). It is possible that a similar disruption of top-down processing of somatosensory stimuli plays a role in the modulation of body ownership by psychedelics (see also Swanson, 2018 for a discussion of the effects of psychedelics on top-down processing).…”
Section: Alterations Of Self-consciousness Induced By Meditation and mentioning
confidence: 99%
“…During dosing sessions, which are embedded in a brief intervention model with preparatory and integrative counseling sessions, therapists usually take a non-directive approach. The patient, who is encouraged to turn attention inward, is mostly lying down, wearing eyeshades, and listening to a carefully selected playlist of music over headphones as the acute psychedelic experience unfolds [for concise summaries of the phenomenology of psychedelic states see (42,43)].…”
Section: Avoidance and Acceptance In Psychedelic Therapymentioning
confidence: 99%